Polarized vs. threshold training intensity distribution on endurance sport performance. a systematic review and meta-analysis of randomized controlled trials - Rosenblat, M. A.; Perrotta, S. A.; Vicenzino, B. (The Journal of Strength and Conditioning Research, 2019)
The objective of this review was to systematically search the literature to identify and analyze data from randomized controlled trials that compare the effects of a polarized training model (POL) vs. a threshold training model (THR) on measurements of sport performance in endurance athletes. This systematic review and meta-analysis is registered with PROSPERO (CRD42016050942). The literature search was performed on November 6, 2016 and included SPORTDiscus (1800-present), CINAHL Complete (1981-present), and Medline with Full Text (1946-present). Studies were selected if they included: random allocation, endurance-trained athletes with greater than 2 years of training experience and VO2max/peak >50 ml/kg·min, a POL group, a THR group, assessed either internal (e.g., VO2max) or external (e.g., time trial) measurements of endurance sport performance. The databases SPORTDiscus, Medline and CINAHL yielded a combined 329 results. Four studies met the inclusion criteria for the qualitative analysis, and 3 for the meta-analysis. Two of the 4 studies included in the review scored a 4/10 on the PEDro Scale and 2 scored a 5/10. With respect to outcome measurements, 3 studies included time-trial performance, 3 included VO2max or VO2peak, 2 studies measured time-to-exhaustion, and one study included exercise economy. There was sufficient data to conduct a meta-analysis on time-trial performance. The pooled results demonstrate a moderate effect (ES = -0.66; 95% CI: -1.17 to -0.15) favoring the POL group over the THR group. These results suggest that POL may lead to a greater improvement in endurance sport performance than THR.